If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7(8 + 2x) = 8 2x + (8 * 7 + 2x * 7) = 8 2x + (56 + 14x) = 8 Reorder the terms: 56 + 2x + 14x = 8 Combine like terms: 2x + 14x = 16x 56 + 16x = 8 Solving 56 + 16x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + 16x = 8 + -56 Combine like terms: 56 + -56 = 0 0 + 16x = 8 + -56 16x = 8 + -56 Combine like terms: 8 + -56 = -48 16x = -48 Divide each side by '16'. x = -3 Simplifying x = -3
| 6(4y+5z)-30z= | | 4log(x-6)=11 | | 16h-13h-2h-1=15 | | (25.12^2)/4(3.14) | | 52=12+4w | | -7/9(x-y+36) | | 2c-c=14 | | (80x-54y)-(62x+9y)= | | 8y-y+2y=18 | | 5(2y+4z)-20z= | | 15+3y=25 | | 4x-5/3x | | 6y(3y-4)+22y= | | (11x+23y)+(38x+50y)= | | -(2x^2-7x+7)= | | 4y(3y-6)+19y= | | A=8*(3.14) | | 4x-6=4(x+5) | | (63x+45y)-(13x+40y)= | | 6(x-6)+20=2(x-6) | | -(12b-10)+5(3b-2)= | | 8x+3=-3+3x+21 | | (23x+64y)+(33x-16y)= | | 4a-2(a+6)= | | a/3=7/10 | | (43x+60y)+(38x-23y)= | | (79x+76y)-(16x+40y)= | | -3x-13=6x+23 | | 16/b=2/3 | | y+3y+2y=12 | | 7a-4(a+6)= | | 6(2y+3z)-18z= |